Therapeutic tactics in the hypothalamic syndrome of puberty in girls. - Borowska-Striuk, T. (Medicni Perspektivi, 2018)
Hypothalamic syndrome of puberty (HSP) is a pathological symptom complex that occurs as a result of dysfunction of hypothalamus, pituitary gland and other endocrine glands during puberty. Purpose – to improve the therapeutic tactics in patients with HSP based on the results of study of the clinical course of the disease, the state of the nervous and endocrine systems. The study included 125 patients aged 11-17 years with HSP, divided into two clinical groups: 50 patients aged 11-14 years and 75 girls aged 15-17 years. The examination included the collection of anamnesis, anthropometric, general clinical and gynecological examination, the study of hormonal profile, lipid and carbohydrate metabolism, instrumental studies, consultations of a neurologist, endocrinologist. It was found that the formation and course of HSP in girls during puberty occurs against a background of perinatal hypoxic involvement of the central nervous system, early obesity, viral loads, disorders of menstrual function, increased secretion of prolactin, androgens, cortisol and reduced level of estradiol. Neurofunctional research methods confirmed the functional nature of changes in the central nervous system in patients with hypothalamic syndrome of puberty. HSP therapy should be comprehensive and systematic, including normalization of body weight, correction of nutrition, mental and physical activity, sleep, thyroid function, hyperandrogenism, insulin resistance, menstrual cycle. In the follow-up dynamics after 2-3 courses of therapy (on average 6-15 months), restoration of the menstrual cycle was observed in all 25 (100%) patients with secondary amenorrhea and regression of cystic ovarian formations in all 11 (100%) patients. Weight loss was noted in most patients with overweight and obesity in 70 (92.1%) cases.